De repente do riso fez-se o pranto: representações e expressões do amor e do sofrimento amoroso - Silva, Vergas Vitória Andrade da (2006)
Romantic love constitutes a central value in the social imaginary of modern societies and with reflexes in today s society. This is because the romantic expectation of realization of love appears, in the majority of cases, as a guarantee of completeness and happiness of individuals. However, the ideal of romantic love imposes a series of demands and character roles that are not easy, in modern age, to be brought about into practice by the ones in love. And, it is in this sense that possible conflicts appear between the romantic proposition and the practical reality of contemporary love. Consequently, the possibility of suffering from love emerges because of these propositions. Initiating from these presumptions, this paper aims to study the contemporary forms of representation and expression of love and of the suffering because of love, through the course of love in the life of some men and women, residents of Natal/RN, that live and/or have lived emotional-sexual relationships, observing the relationship that can be established between suffering from love and the ideal romantic love